Trust, Salience and Deterrence: Evidence from an Antitrust Experiment - Maria Bigoni; Sven-Olof Fridolfsson; Chloe Le Coq; Giancarlo Spagnolo (Research Institute of Industrial Economics (IFN), 2011)
We present results from a laboratory experiment identifying the main channels through which different law enforcement strategies deter organized economic crime. The absolute level of a fine has a strong deterrence effect, even when the exogenous probability of apprehension is zero. This effect appears to be driven by distrust or fear of betrayal, as it increases significantly when the incentives to betray partners are strengthened by policies offering amnesty to turncoat whistleblowers. We also document a strong deterrence effect of the sum of fines paid in the past, which suggests a significant role for salience or availability heuristic in law enforcement.
Keywords: C92; D03; D80; K21; K42; L41; 330; Betrayal; Collusion; Corruption; Distrust; Fraud; Organized Crime; Whistleblowers; Wirtschaftskriminalität; Kartell; Whistleblowing; Kartellrecht; Test; Schweden